Assessing consumers' satisfaction and expectations through online opinions: Expectation and disconfirmation approach. (October 2017) - Qazi, Atika; Tamjidyamcholo, Alireza; Raj, Ram Gopal; Hardaker, Glenn; Standing, Craig
Abstract: The opportunity to capture the opinions of the general public about multiple topics such as social events, marketing campaigns, and product preferences has raised more and more interest in the business world. This paper aims to find the users' level of expectation associated with multiple types of opinion. In addition, the study also aims to find the effect of sentiment words on customer satisfaction at the post-purchase stage. In this work, the positive, negative and neutral sentiment words relating to the users' satisfaction were analysed. Firstly, the questionnaire comprising seven sections was proposed to collect data. The study used the expectancy disconfirmation theory (EDT), and a set of seven hypotheses. Confirmatory factor analysis (CFA) and structural equation modelling (SEM) were used to analyse the data and evaluate the research model. The findings of this study imply that regular, comparative and suggestive opinions have a positive effect in raising users' expectations. This study also predicted a strong relationship between expectation, performance and disconfirmation. In addition, sentiment words proved to be a full mediator in predicting user satisfaction with a purchased item. Highlights: Customers' expectations and satisfaction with multiple opinion types is studied. Sentiment words proved to be full mediator in predicting user's satisfaction. Regular, comparative and suggestive opinions positively effects on expectations. Comparative opinions are more influential in arising users' expectation.